2011
DOI: 10.1007/s00425-011-1560-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence kinetic parameters and cyclic electron transport in guard cell chloroplasts of chlorophyll-deficient leaf tissues from variegated weeping fig (Ficus benjamina L.)

Abstract: Residual chlorophyll in chlorophyll-deficient (albino) areas of variegated leaves of Ficus benjamina originates from guard cell chloroplasts. Photosynthetic features of green and albino sectors of F. benjamina were studied by imaging the distribution of the fluorescence decrease ratio Rfd within a leaf calculated from maximum (Fm) and steady-state leaf chlorophyll fluorescence (Fs) at 690 and 740 nm. Local areas of albino sectors demonstrated an abnormally high Rfd(740)/Rfd(690) ratio. Fluorescence transients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…Thus we showed that only a Cyclic Electron Transport (CET-PSII or/and CET-PSI) occurs in the stomata cells thylakoids of albino leaf sectors of variegated Ficus benjamina plants under excitation by blue light whereas a non-cyclic electron transport is absent. Such a conclusion was based, among other facts, on the absence of any changes of chlorophyll fluorescence excited at 470 nm in response to the applying of the supplementary far-red light (Lysenko, 2012). In contrast, normal green tissues possessing a non-cyclic electron transport, show a clear increase of photochemical fluorescence quenching in this case, that was first discovered by Govindjee and Rabinowitch (1960) and confirmed in our work (Lysenko, 2012).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Thus we showed that only a Cyclic Electron Transport (CET-PSII or/and CET-PSI) occurs in the stomata cells thylakoids of albino leaf sectors of variegated Ficus benjamina plants under excitation by blue light whereas a non-cyclic electron transport is absent. Such a conclusion was based, among other facts, on the absence of any changes of chlorophyll fluorescence excited at 470 nm in response to the applying of the supplementary far-red light (Lysenko, 2012). In contrast, normal green tissues possessing a non-cyclic electron transport, show a clear increase of photochemical fluorescence quenching in this case, that was first discovered by Govindjee and Rabinowitch (1960) and confirmed in our work (Lysenko, 2012).…”
Section: Introductionsupporting
confidence: 65%
“…Besides, far-red light can be used in dualwavelength excitation experiments to test PSI and PSII coupling within a single linear electron transport chain (Lysenko, 2012). Thus we showed that only a Cyclic Electron Transport (CET-PSII or/and CET-PSI) occurs in the stomata cells thylakoids of albino leaf sectors of variegated Ficus benjamina plants under excitation by blue light whereas a non-cyclic electron transport is absent.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In our preliminary studies with P. hybrida flower petals, such a “short pulse” technique produced a sufficiently higher ES (8–10%) compared to that of the commonly used “long pulse” method (ES < 2%); this result is most likely due to the high instantaneous light intensity of the pulse, adapting the proposed ADAPFP to be more efficient. It should be noted here that the “short pulse” technique can be applied only when the PA signal is processed using fast Fourier transform instead of the commonly used lock-in amplifier as described in our previous work14.…”
Section: Resultsmentioning
confidence: 99%